2011
DOI: 10.1001/jama.2011.1019
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Long-term Effects of Chemotherapy in Young Women With Early-Stage Breast Cancer

Abstract: A LTHOUGH THE MEDIAN AGE OF WOMEN DIAGnosed with breast cancer is 61 years, about 35% of women newly diagnosed with breast cancer are 54 years or younger, and 12%-almost 25 000-are younger than 45 years.1 The majority of women with breast cancer will receive adjuvant therapy including chemotherapy, hormone therapy, or both, which has been documented to improve disease-free and overall survival. Treatment has a number of adverse effects that directly affect short-term and, in some cases, long-term quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Since GnRH receptors are expressed by a variety of cancers and mediate several effects (e.g., inhibition of proliferation, induction of cell-cycle arrest, and inhibition of apoptosis), it has been suggested that the concomitant administration of GnRH agonist therapy might antagonize CT, reducing its efficacy [84,85]. Therefore, ovarian suppression with GnRH agonists might be safer in women with estrogen receptor-negative BC [86]. Detrimental effects of GnRH agonists on patients under CT, however, were not shown in clinical trials.…”
Section: Preserving Fertility In Breast Cancer Patientsmentioning
confidence: 99%
“…Since GnRH receptors are expressed by a variety of cancers and mediate several effects (e.g., inhibition of proliferation, induction of cell-cycle arrest, and inhibition of apoptosis), it has been suggested that the concomitant administration of GnRH agonist therapy might antagonize CT, reducing its efficacy [84,85]. Therefore, ovarian suppression with GnRH agonists might be safer in women with estrogen receptor-negative BC [86]. Detrimental effects of GnRH agonists on patients under CT, however, were not shown in clinical trials.…”
Section: Preserving Fertility In Breast Cancer Patientsmentioning
confidence: 99%
“…An association between such biomarkers and important clinical outcomes like infertility has yet to be clearly established amongst a diverse group of cancers. An ability to better predict increased risk for reproductive difficulties after treatment could improve counseling for the 123,000 reproductive-age women diagnosed with cancer each year in the United States [2,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent studies have demonstrated that even women who continue to menstruate after treatment also remain at increased risk of infertility and early menopause [1,18,19]. Thus, at least in part due to treatment, some women lose their ability to conceive children naturally and others experience significant compromise from a shortened reproductive window [2,3,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] In the past, when assessing the gonadotoxicity of cancer treatments, most studies used the presence or absence of normal menses as their primary outcome. 15,16 This approach had limitations in terms of improving our understanding of fertility and premature menopause as outcomes remote from treatment. Albright et al first described primary ovarian insufficiency (also known as premature ovarian failure) in 1942 17,18 ; since then an increased understanding has been gained regarding partial ovarian injury.…”
Section: Cancer Treatment As An Accelerator Of Ovarian Agementioning
confidence: 99%